2018
DOI: 10.1101/411074
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discerning the functional networks behind processing of music and speech through human vocalizations

Abstract: Musicality refers to specific biological traits that allow us to perceive, generate and enjoy music. These abilities can be studied at different organizational levels (e.g., behavioural, physiological, evolutionary), and all of them reflect that music and speech processing are two different cognitive domains. Previous research has shown evidence of this functional divergence in auditory cortical regions in the s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…The PPo is associated with many sound processing functions, such as pitch chroma ( Warren et al. 2003 ) and melodic aspects of human vocalizations ( Angulo-Perkins and Concha 2019 ). Unlike the PPo, the very anterior and posterior regions of STC are assumed to be higher-order association areas, especially for the multimodal integration of social information ( Kreifelts et al.…”
Section: Discussionmentioning
confidence: 99%
“…The PPo is associated with many sound processing functions, such as pitch chroma ( Warren et al. 2003 ) and melodic aspects of human vocalizations ( Angulo-Perkins and Concha 2019 ). Unlike the PPo, the very anterior and posterior regions of STC are assumed to be higher-order association areas, especially for the multimodal integration of social information ( Kreifelts et al.…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting a scale with a non-scale condition is thus one way to reveal tonality-specific brain regions. Studies that have directly contrasted music with non-musical functions like speech have revealed the importance of the aSTG bilaterally for music (Angulo-Perkins et al, 2014; Angulo-Perkins & Concha, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that our tonality meta-analysis did not show a cluster in the right temporal lobe, except for a right pSTG cluster that emerged when the cluster-forming threshold was reduced beyond the standard threshold of p < 0.001. Nevertheless, studies that have directly contrasted music with speech highlight the importance of the bilateral aSTG for music (Angulo-Perkins et al, 2014; Angulo-Perkins & Concha, 2019), and a study on pitch-based hierarchical structure building reported activation in the right pSTG (Martins et al, 2020). Thus, the specificity of the right temporal lobe for higher-level tonal processing needs further clarification, despite the well-established role of this area in low-level pitch processing for music (Zatorre et al, 1994, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For our study, 89 articles 47–132 were extracted from the Google Scholar and PubMed databases using the keywords “neuroplasticity,” “brain changes,” “music,” and “sound.” Based on these keywords, we included all articles that were published in 2019, written in English, and peer‐reviewed. The sample included both quantitative and qualitative studies.…”
Section: Methodsmentioning
confidence: 99%